Unlocking Tourism Potential: Tourism Innovations in Increasing Village Original Income - Mailoa, Rivan Jonea; Ohoiwutun, Stanislaus Kostka; Rahanra, Ivvony Yeany (Universitas Pattimura, 2023)
This article aims to describe strategies for increasing Village Original Income (PADes) through optimizing tourism potential in Negeri Latuhalat, Ambon City. The study employs a qualitative approach using in-depth interviews and direct observation to gather data on local potentials and challenges. The findings reveal that Negeri Latuhalat possesses significant natural, cultural, and historical assets that remain underutilized for tourism sector development. The analysis highlights the need for infrastructure development, sustainable tourism program design, and enhanced community involvement as key steps in advancing tourism innovations. This study offers a comprehensive and fresh approach, focusing not only on economic growth but also on social and environmental sustainability. The strategic recommendations include community empowerment, establishing partnerships between government and private sectors, and leveraging digital-based promotion to expand tourism appeal. This article provides valuable contributions to the development of social sciences and humanities, particularly in crafting community-based policies to support rural tourism. With proper implementation, these strategies are expected to significantly enhance PADes while strengthening local identity and improving community well-being.